Exploring the Roles and Challenges of the Sandwich Generation in the Context of Islamic Education and Family Ethics - Tanuri Tanuri (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This article aims to analyze the challenges faced by the sandwich generation from the perspective of Islamic education, while also offering solutions grounded in Islamic values. The main problem raised is the imbalance of roles and weak spiritual resilience in facing the pressures of life. The method used is a literature study with a descriptive qualitative approach, using data from the Qur'an, Hadith, as well as classical and contemporary literature in Islamic education. The novelty of this article lies in the integration of Islamic educational principles such as birrul walidain, responsibility (amanah), patience, and tawakal as the foundation for building the mental and spiritual resilience of the sandwich generation. The results of the study show that Islamic education is able to provide a solid foundation of values to face the complexity of this dual role. In conclusion, the continuous internalization of Islamic educational values can be a constructive solution in maintaining the balance of life of the sandwich generation spiritually, socially, and psychologically, The phenomenon of the sandwich generation refers to a group of adult individuals who are squeezed with the dual responsibility of meeting the living needs of their parents and children simultaneously. This condition not only creates economic pressure, but also has a significant impact on emotional and spiritual stability.